Direito(s) e(m) movimento(s): assessoria jurídica popular a movimentos populares organizados em torno do direito à terra e ao território em meio rural no Ceará - Martins, Martha Priscylla Monteiro Joca (2011)
This dissertation aims to investigate the praxis of the Juridical Popular Assistance to organized popular movements in the struggle for land and territory in rural country of Ceará. For this purpose, have been combined bibliographic and field researches, through interviews, focus groups, rounds of conversation, informal dialogues, participant observation with attorneys of the National Network of Popular Lawyers in Ceará and members of social movements assisted by them, in their search for equity in access to land and land occupation in Ceará. Results indicate that these movements, in their vindicating struggles and resistance, in multiethnic and multicultural perspectives, produce meanings of land and territory rights that lead to the problematization of hegemonic legal culture as a field of possible realization of these rights. Those Lawyers working together with their advised popular movements, constitute legal and political strategies that strengthen the struggles of popular movements in achieving their territorial rights, and incite the constitution of other legal cultures conducive to achieving the Human Right to Land and Territory in its intercultural and critical perspective.